THE EFFECT OF MATERIALISM AND FRUGALITY ON OVER-INDEBTEDNESS. THE MODERATING ROLE OF FINANCIAL LITERACY - Maria Maria (SEAN Institute, 2023)
The present study’ objective was to inspect the impact of materialism and frugality toward over-indebtedness as moderated by financial literacy. Data were gained from employees in a major city in Indonesia. Through a quantitative approach, a Structural Equation Modelling analysis was conducted to draw conclusions. The results suggest that financial literacy moderated the relationship between materialism and over-indebtedness, as well as the link between frugality and over-indebtedness. The practical benefits obtained can be used by managers in general to improve employee welfare by avoiding over-indebtedness.